P2Y6 Receptor-Mediated Proinflammatory Signaling in Human Bronchial Epithelia - Hao, Yuan; Liang, Jocelyn F.; Chow, Alison W.; Cheung, Wing-tai; Ko, Wing-hung (PLOS ONE, 2014)
P2Y receptors are expressed in virtually all epithelia and are responsible for the control of fluid and electrolyte transport. In asthmatic inflammation, the bronchial epithelia are damaged by eosinophil-derived, highly toxic cationic proteins, such as major basic protein (MBP). Consequently, extracellular nucleotides are released into the extracellular space from airway epithelial cells, and act in an autocrine or paracrine fashion to regulate immune functions. Our data show damage to the human bronchial epithelial cell line, 16HBE14o-, by poly-L-arginine-induced UDP release into the extracellular medium. Activation of P2Y6 receptor by its natural ligand, UDP, or its specific agonist, MRS 2693, led to the production of two proinflammatory cytokines, interleukin (IL)-6 and IL-8. This may have resulted from increased IL-6 and IL-8 mRNA expression, and activation of p38 and ERK1/2 MAPK, and NF-κB pathways. Our previous study demonstrated that UDP stimulated transepithelial Cl− secretion via both Ca2+- and cAMP-dependent pathways in 16HBE14o- epithelia. This was further confirmed in this study by simultaneous imaging of Ca2+ and cAMP levels in single cells using the Fura-2 fluorescence technique and a FRET-based approach, respectively. Moreover, the P2Y6 receptor-mediated production of IL-6 and IL-8 was found to be dependent on Ca2+, but not the cAMP/PKA pathway. Together, these studies show that nucleotides released during the airway inflammatory processes will activate P2Y6 receptors, which will lead to further release of inflammatory cytokines. The secretion of cytokines and the formation of such “cytokine networks” play an important role in sustaining the airway inflammatory disease.